Revolusi Dakwah Digital 4.0: Menjangkau Jamaah Melalui Teknologi Informasi di PCM Tanjung Karang - Astutik, Fitri; Mu'adz, Hendra Iqranul; Albi, Allen; Zohri, M Afriandi; Syawaludin, Syawaludin; Hafiz, Abdul; Fadilah, Putri Nurul (Puslitbang Sekawan Institute Nusa Tenggara, 2025)
This community service program aims to implement the digital da'wah revolution 4.0 at PCM Tanjung Karang by utilizing information technology to reach a broader and more effective audience. In the PCM Tanjung Karang area, religious activities conducted in mosques have not been well-documented, and the use of technology in da'wah remains limited. Consequently, there are constraints in disseminating information to the congregation. To address this issue, this program proposes the development and management of social media platforms and an official PCM Tanjung Karang website as tools for documenting, publishing, and accessing da'wah activities. Additionally, digital media management training for mosque administrators, as well as the preparation of activity calendars and reports in digital formats, are carried out to enhance the capacity of mosque administrators in managing technology-based da'wah. The results of this initiative indicate a significant improvement in the documentation and publication of da'wah activities, as well as easier access to information for the congregation. Although there are certain challenges in managing digital platforms, this program is expected to serve as an effective and sustainable model for digital da'wah implementation in other mosques within the region.